2019
DOI: 10.3390/jdb7040020
|View full text |Cite
|
Sign up to set email alerts
|

Axin Family of Scaffolding Proteins in Development: Lessons from C. elegans

Abstract: Scaffold proteins serve important roles in cellular signaling by integrating inputs from multiple signaling molecules to regulate downstream effectors that, in turn, carry out specific biological functions. One such protein, Axin, represents a major evolutionarily conserved scaffold protein in metazoans that participates in the WNT pathway and other pathways to regulate diverse cellular processes. This review summarizes the vast amount of literature on the regulation and functions of the Axin family of genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 163 publications
1
27
1
Order By: Relevance
“…The involvement of PRY-1 in multiple signaling pathways and biological events is well documented (Mallick et al, 2019a). Earlier, we reported both mRNA and microRNA (miRNA) transcriptome profiles of pry-1 mutant that revealed 2,665 differentially expressed (DE) proteincoding genes and six miRNAs (Mallick et al, 2019b;Ranawade et al, 2018).…”
Section: Pry-1 Transcriptome Contains Genes Involved In Lifespan Regumentioning
confidence: 94%
See 3 more Smart Citations
“…The involvement of PRY-1 in multiple signaling pathways and biological events is well documented (Mallick et al, 2019a). Earlier, we reported both mRNA and microRNA (miRNA) transcriptome profiles of pry-1 mutant that revealed 2,665 differentially expressed (DE) proteincoding genes and six miRNAs (Mallick et al, 2019b;Ranawade et al, 2018).…”
Section: Pry-1 Transcriptome Contains Genes Involved In Lifespan Regumentioning
confidence: 94%
“…A similar phenotype is also observed in a CRISPR allele, gk3682, that deletes roughly 750 bp region including the 5' UTR and first exon (Mallick et al, 2019b) ( Figure 1C; Table S2). As pry-1 is also involved in developmental processes (Mallick et al, 2019a), we took an RNAi approach to knock down the gene function specifically during adulthood. As expected, pry-1(RNAi) animals were found to be short-lived, with a 22-31% reduction in the mean lifespan ( Figure 1D; Table S2).…”
Section: Mutations In Pry-1 Reduce the Lifespanmentioning
confidence: 99%
See 2 more Smart Citations
“…Variants of AXIN1 and AXIN2 genes, or of the other components of the signaling pathway, may influence the gene activity and also β-catenin mRNA levels [ 7 ], therefore, being involved in the development and/or progression of diseases such as cryptorchidism [ 8 ], congenital septal heart defects [ 9 ], hepatocellular carcinoma [ 10 ], colorectal carcinoma [ 11 ], and lung and other types of cancers [ 12 ]. Previous experimental studies demonstrated that AXIN1 and AXIN2 had a crucial role in cell proliferation and heart development [ 13 ]. Also, experimental studies such as the study performed by Lei Ji et al [ 14 ] confirmed that several variants of AXIN1 and AXIN2 genes were pathogenic variants associated with heart abnormalities [ 14 ].…”
Section: Introductionmentioning
confidence: 99%